Correlações entre maturação biológica e aptidão física em jovens praticantes de karatê - MONTEIRO, Marco Antônio Pereira (2019)
The importance of studying biological maturation is that maturity may be related to both physical fitness and the variability found is not neuromuscular in children and young people. Thus, the objective of the research was to verify the biological maturity, through the age of the Peak of Growth Velocity (PVC); and relate to the physical fitness of young karate practitioners. It participates in the study, 46 male and female with the age group of eight to twelve years. To verify maturation through PVC, measurements of body mass, height, sitting height and birth data were performed. Physical fitness has already been analyzed, the test manual and the evaluation of the Brazilian Sports Project (PROESP / Br) have been used. The results of the higher education session with more advanced maturity levels, belonging to the same age group, tended to be an indicator of superior results in the medicineball throw and horizontal jump tests. The maturation of the age group of 8 to 12 years, a biological maturation had a relation with the medicineball pitch (r = 0.754, p = 0.000). In the age group of 8 to 10 years, a biological maturation had the medicineball pitch ratio (r = 0.735; p = 0.000). In the age group of 11 to 12 years, biological maturation had as function the two testicles, which were: medicineball pitch (r = 0.766; p = 0.000) and horizontal jump (r = 0.592; p = 0.010). Compared to results, biological maturation is concluded, it has a relationship with the medicineball pitch and horizontal jump tests.